T Cells in Autoimmunity-Associated Cardiovascular Diseases - Schwartz, Daniella Muallem; Burma, Aarohan M.; Kitakule, Moses M.; Luo, Yiming; Mehta, Nehal N. (Frontiers in Immunology, 2020)
T cells are indisputably critical mediators of atherosclerotic cardiovascular disease (CVD), where they secrete pro-inflammatory cytokines that promote vascular pathology. Equally well-established is the fact that autoimmune diseases, which are mediated by autoreactive T cells, substantially increase the risk of developing CVD. Indeed, as immunomodulatory treatments have become more effective at treating end-organ pathology, CVD has become a leading cause of death in patients with autoimmune diseases. Despite this, investigators have only recently begun to probe the mechanisms by which autoreactive T cells promote CVD in the context of autoimmune diseases. Herein, we review the role of T cells in vascular inflammation associated with four autoimmune diseases. T cells are best-studied in the pathogenesis of systemic vasculitides, where they react to self-antigen in the vessel wall. However, newer studies indicate that T cells also contribute to the increased CVD risk associated with lupus and rheumatoid arthritis. Given the central role of T-cell-derived cytokines in the pathogenesis of psoriasis, the role of these factors in psoriatic CVD is also under investigation. In the future, T cells are likely to represent major targets for the prevention and treatment of CVD in patients with autoimmune diseases.